Increasing effort without noticing: A randomized controlled pilot study about the ergogenic placebo effect in endurance athletes and the role of supplement salience. - Ellen K Broelz; Sebastian Wolf; Patrick Schneeweiss; Andreas M Niess; Paul Enck; Katja Weimer (PLoS ONE)
Purpose Previous research shows that endurance performance can be enhanced by placebo ergogenic aids. This study investigates the ergogenic placebo response, which we define as an increase in objective and physiological effort without an increase in subjective effort, in competitive cyclists. The primary objective of this study is to explore the role of supplement salience in the ergogenic placebo response, while the secondary aim is to assess whether believing to have taken an inactive placebo supplement attenuates the desired ergogenic effect. Methods We employed a double-blind placebo-controlled study design and compared a high salience (pudding) to a low salience (capsules) ergogenic placebo supplement and to a no treatment control group. Thirty-four male athletes (30.0 ± 5.7 years) performed two self-regulated time trials on an isokinetic cycling ergometer, one without intervention serving as a baseline and one with intervention according to group assignment. At both time trials, power output (objective effort), blood lactate (physiological effort) and the rating of perceived exertion (subjective effort) were measured. Results Receiving a high salience supplement can increase physiological and objective effort without a proportional rise in subjective effort, suggesting a decoupling of perceived exertion and endurance performance. Low salience and control group both showed no such ergogenic placebo response. Athletes' belief concerning the true nature of the ergogenic aid (inactive placebo vs. ergogenic supplement) did not influence the ergogenic placebo response. Conclusion High salience placebo ergogenic aids can elicit enhanced performance without the athlete noticing (exertion), and deception of athletes seems unnecessary as even believing to have received an inactive placebo supplement maintains the ergogenic placebo response.